2022
DOI: 10.1002/adfm.202204352
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Deep‐Blue Organic Light‐Emitting Diodes Based on Rational Molecular Design and Device Engineering

Abstract: There is increasing interest in thermally activated delayed fluorescence (TADF) in materials, and to understand its mechanism in the excited state dynamics. Recent challenges include color purity, efficient deep-blue emission, fast exciton decay lifetimes, high reverse intersystem crossing rates (k RISC ), low-efficiency roll-off in organic light-emitting diodes (OLEDs), and long device lifetimes. Here, a series of compounds having benzonitrile and carbazole rings are examined, that provide a detailed understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 76 publications
1
22
0
Order By: Relevance
“…Recently, Adachi et al developed multiple donor and acceptor blue TADF materials to sensitize v-DABNA. 63 The four donors and two acceptors (4PhCz2BN) exhibited a fast RISC process (k RISC 4 10 6 s À1 ) resulting from the dense alignments of 1 CT, 3 CT, and 3 LE. The material also exhibited k r 4 10 7 s À1 .…”
Section: Tadf-sensitized Mr-tadf Oledsmentioning
confidence: 99%
“…Recently, Adachi et al developed multiple donor and acceptor blue TADF materials to sensitize v-DABNA. 63 The four donors and two acceptors (4PhCz2BN) exhibited a fast RISC process (k RISC 4 10 6 s À1 ) resulting from the dense alignments of 1 CT, 3 CT, and 3 LE. The material also exhibited k r 4 10 7 s À1 .…”
Section: Tadf-sensitized Mr-tadf Oledsmentioning
confidence: 99%
“…In this work, we extract the effect of hydrogen bonding using the clathrate crystal with TADF and H 2 O molecules. We found that the crystal of TADF material 4Cz2BN (Figure a) contains H 2 O molecules despite the crystal preparation by sublimation under a high vacuum (10 –2 Pa), indicating the existence of the insertion path of H 2 O molecules and the formation of the clathrate after exposure to air . The hydrogen bonding may change the CT strength of the TADF molecule because the LUMO of the proton acceptor will decrease .…”
mentioning
confidence: 94%
“…The molecular structure is primarily important for realizing efficient RISC because charge transfer (CT) minimizing wave function overlap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) is basically the key for the small singlet–triplet gap (Δ E ST ). Moreover, the alignment of the local excitation triplet ( 3 LE) and CT triplet ( 3 CT), which contributes to second-order spin–orbit coupling accelerating RISC, has also been controlled by appropriate molecular design. Meanwhile, external factors such as polarization and structural constraint through intermolecular interactions from surrounding media such as solvents, host materials, and itself also have a significant impact on the excited state dynamics of TADF materials. Triplet exciton management, e.g., increasing the RISC rate constant ( k RISC ) to reduce the level of triplet accumulation, is considered to be a basic approach to increasing device durability, which is a critical demand of the OLED industry …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, to harvest all electrically generated excitons as EL, various strategies for emissive materials have been studied. One approach is the utilization of highly emissive room-temperature phosphorescence materials such as an iridium or platinum complex, allowing for nearly 100% internal EL quantum efficiency (IQE) by radiatively decaying triplets to the ground state. Another strategy is to convert all dark triplets to an excited singlet state with the help of thermal energy, known as the thermally activated delayed fluorescence (TADF) process. Despite the fact that these OLEDs exhibit promising potential for achieving optimal IQE in blue OLEDs, they still suffer from relatively limited operational device lifetime compared to green and red OLEDs, likely due to their high excited triplet energy (∼2.8 eV) that induces unwarranted degradation events. …”
Section: Introductionmentioning
confidence: 99%